Editorial - ., Sociedad Mexicana de Ingeneiria Biomedic (Revista Mexicana de Ingenieria Biomedica, 2018)
We put the second issue of our magazine in this new stage for our readers’ consideration. Efforts have been great for its publication but we are convinced that maintaining the continuity and good quality of its content is worthwhile as it presents our society as a group of professionals, technicians and researchers who with their work provide solutions to the problems that arise in our country in our field.